2014
DOI: 10.7314/apjcp.2014.15.16.6829
|View full text |Cite
|
Sign up to set email alerts
|

FNC, a Novel Nucleoside Analogue, Blocks Invasion of Aggressive Non-Hodgkin Lymphoma Cell Lines Via Inhibition of the Wnt/β-Catenin Signaling Pathway

Abstract: Chemotherapy is the primary therapy for malignant lymphoma (ML). However, the clinical outcome is still far from satisfactory. Consequently, an understanding of the mechanism of modulating cancer cell invasion, migration and metastasis is important for the development of more effective chemotherapeutic agents. FNC, 2'-deoxy-2' -β-fluoro -4'-azidocytidine, a novel cytidine analogue, has demonstrated significantly inhibitory effects on proliferation of several non-Hodgkin lymphoma (NHL) cell lines. A previous st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Invasion and metastasis are important biological characteristics of malignant tumors. The processes are quite complicated and involve multiple molecular mechanisms, including the adhesion, migration and invasion . Cadherins are a family of transmembrane glycoproteins that play an indispensable role in intercellular adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…Invasion and metastasis are important biological characteristics of malignant tumors. The processes are quite complicated and involve multiple molecular mechanisms, including the adhesion, migration and invasion . Cadherins are a family of transmembrane glycoproteins that play an indispensable role in intercellular adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…Similar effects were also seen in various human cancer cell lines, such as lung adenocarcinoma and acute myeloid leukemia[15]. Furthermore, FNC could remarkably inhibit the adhesion, migration and invasion of Raji and JeKo-1 cell lines[16]. Based on our previous work, the mantle cell lymphoma cell line JeKo-1 was chosen to further study the effects of FNC on the proliferation of MCL and its molecular mechanism, providing an experimental basis for the early clinical application of FNC.…”
Section: Introductionmentioning
confidence: 65%
“…They transduce cell proliferation and transformation signals through the phosphorylation and activation of PI3K/AKT, thereby inhibiting apoptosis. Zhang et al (2014) found when studying the non-hodgkin lymphoma that the activation of Wnt/β-catenin signal pathway could induce the downregulation of β-catenin and high expression of E-cadherin thus reducing the expressions of cytoadherence and tumor invasion-related proteins, which finally could inhibit the growth of tumors.We found that E-cadherin and β-catenin gene expression and protein translation were at lower levels in the experimental group than in the control group. However, the expression of caspase-3 was increased in the experimental group compared to the control group.…”
Section: Discussionmentioning
confidence: 99%